PERDAMAIAN DALAM ISLAM DAN BUDDHA PERSPEKTIF AL-QUR’AN DAN TRIPITAKA: Perspectives from the Qur’an and the Tripitaka - Hidayah, Alfa Handi; Kusumawati, Devi; Al-Ghifari Syatta, Muhammad Miqdad (Al Hikmah, 2025)
Indonesia, as a multireligious country, faces challenges of conflicts often carried out in the name of religion. The Qur’an and Tripitaka, as the sacred texts of Islam and Buddhism, teach values of peace, tolerance, and harmony that can serve as solutions to interfaith conflicts. This study aims to compare the concepts of peace in the Qur’an and Tripitaka, analyze their similarities and differences, and evaluate the application of these values in resolving interreligious conflicts. The research adopts a qualitative approach using a comparative study method. Data were collected through textual analysis of the Qur’an and Tripitaka as primary sources, along with relevant secondary literature. The analysis identified peace concepts and their social relevance. The findings reveal that the Qur’an emphasizes peace through Iṣlāḥ (reconciliation) and Salám (peace), while the Tripitaka highlights Metta (loving-kindness), Karuna (compassion), and Upekkha (equanimity). Both religions reject violence, with Islam focusing more on practical solutions, while Buddhism emphasizes individual transformation. The peace concepts in the Qur’an and Tripitaka can form the foundation for interfaith dialogue, fostering tolerance and harmony in society. Implementing these values is crucial to resolving conflicts in diverse communities and promoting interreligious harmony.